Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/ma971827p
|View full text |Cite
|
Sign up to set email alerts
|

Self-Ordering within Thin Films of Poly(olefin sulfone)s

Abstract: A study has been performed of the manner in which two structural features of poly(olefin sulfone)s, helical backbones and calamitic side chains, create order in films. For this purpose copolymers were prepared with one (polymer I) or two (polymer III) cyanobiphenyls per residue, and terpolymers were prepared with both such residues diluted to below the 5% level within an otherwise poly(eicosene sulfone) chain (respectively, polymers II and IV). The polymers all have ordered phases according to X-ray powder dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
5
37
0
Order By: Relevance
“…No differences between the position of absorption maximum in film and in solution are observed (3b-d, 4f-h) in the case of all polymers except for polymer 3a(4e). The p-p * transition of the azobenzene in the film is 18 nm hypsochromically shifted with respect to the solution which indicates the formation of H aggregates [22]. …”
Section: Synthesis and Characterization Of Poly(amide Imide)smentioning
confidence: 96%
“…No differences between the position of absorption maximum in film and in solution are observed (3b-d, 4f-h) in the case of all polymers except for polymer 3a(4e). The p-p * transition of the azobenzene in the film is 18 nm hypsochromically shifted with respect to the solution which indicates the formation of H aggregates [22]. …”
Section: Synthesis and Characterization Of Poly(amide Imide)smentioning
confidence: 96%
“…It was reported that the mesogenic groups aligned homeotropically by heating for the polymer LC films with azobenzene side groups [24] and cyanobiphenyl side groups. [28] The length of the spacer between the polymer backbone and the mesogenic groups, and the type of the polymer main chain influence the homeotropic alignment by annealing. [24,28] In the case of the P2 film, the formation of the polydomain structure of the mesogenic groups, and the interaction between the mesogenic groups and the glass substrate during the annealing will be highly changed when the heating rate is changed, resulting in the different re-orientational behavior.…”
Section: Discussionmentioning
confidence: 99%
“…[28] The length of the spacer between the polymer backbone and the mesogenic groups, and the type of the polymer main chain influence the homeotropic alignment by annealing. [24,28] In the case of the P2 film, the formation of the polydomain structure of the mesogenic groups, and the interaction between the mesogenic groups and the glass substrate during the annealing will be highly changed when the heating rate is changed, resulting in the different re-orientational behavior. Further study on the alignment behavior using CPLCs with a 6CiB group and an nCB group with spacers of different lengths is still underway.…”
Section: Discussionmentioning
confidence: 99%
“…The CD spectra of the irradiated polymers exhibit an exciton couplet corresponding to the p À p à absortion band of the azobenzene and centered between 330 and 340 nm, that is blue-shifted in comparison to the p À p à absorption band of the UV-vis spectra corresponding to isolated azobenzene groups [20,21]. These exciton couplets are due to the splitting of an H-band as a consequence of a chiral interaction between adjacent chromophores [27][28][29]. The Cotton effect at 390 nm can be due to the superposition of the band of the exciton couplet centered around 330-340 nm, the induced Cotton effects of the isolated azobenzene units and J-aggregates [30].…”
Section: A Azopolymersmentioning
confidence: 99%